HIV-1 subtype C protease: enzyme kinetics, thermodynamics, and X-ray crystal structure - Dlamini, Nozinhle Precious (University of the Witwatersrand, Johannesburg, 2023)
Human immunodeficiency virus (HIV), a precursor for AIDS is still one of the most devastating pandemics in history. In 2021 alone there were 650 000 deaths associated with the virus and the number of people living with the infection was recorded to be 38.4 million globally. Sub-Saharan Africa suffers the most burden of the virus with approximately 8.3 million people living with virus, HIV-1 subtype C is the main driver of the disease in South Africa and accounts for 46% of global infections. Even with these alarming statistics this subtype is not the main focus point for the majority of HIV-1 research which mainly focuses on subtype B though it only accounts for 12% of infections globally. There is no vaccine or cure against HIV; however, great strides have been made in suppressing the virus. Viral suppression drugs have been developed to target different stages of viral replication such as those targeting the three important enzymes (protease, reverse transcriptase and integrase). In this study the focus will be on HIV-1 subtype C protease. This is a homodimeric aspartyl protease with 99 amino acids in each monomer. It plays a crucial role in the replication cycle of HIV-1 by producing mature infectious virions through cleavage of the Gag and Gag-Pol polyproteins. The subtype C protease differs from subtype B protease in that it has eight naturally occurring polymorphisms which are substitution mutations, some occurring in different regions of the protease with some in the fulcrum (T12S, I15V and L19I), others in the hinge region (M36I and R41K), with H69K and L89M found in the loops and I93L in the α helix. In this study, structural and functional characterisation of HIV-1 subtype C protease was carried out. The secondary structure was characterised using far-UV CD, which is a technique that measures the difference in left and right circularly polarised light. The subtype C protease was estimated to be predominantly β-sheeted, with spectra showing a maximum at 195 nm and a minimum between 215-225 nm. Tertiary structure characterisation of protease was performed using fluorescence spectroscopy. The maximum emission at 347 nm close to that of water (350 nm), demonstrated that the tertiary conformation of the HIV-1 protease was conserved, and that the tryptophan residues within the protease are solvent exposed. SE-HPLC was used to characterise the quaternary structure of the protease and the homodimeric size was determined to be approximately 22 kDa. Steady-state enzyme kinetics to assess the catalytic activity of the subtype C protease was performed using a fluorogenic substrate. The activity of the enzyme was confirmed, with the specific activity of 24.22±1.72 µmol. min-1.mg-1 and the binding of the substrate to the HIV-1 protease was demonstrated by the KM value of 79.546±6.491 µM. This correlates to literature indicating that the substrate was weakly bound and that a high substrate concentration will be required to reach the maximum velocity (Vmax), and Vmax was determined to be 0.036±0.003 µmol. min-1. Enzyme kinetics was coupled with displacement isothermal titration calorimetry for determination of thermodynamics parameters using second generation PIs (atazanavir, darunavir and lopinavir). Thermodynamic studies indicated that the HIV-1 protease has a high affinity for LPV (Kd = 1 nM), compared to ATV (Kd = 18.57nM) and DRV (Kd = 42.26 nM) and binding reactions were all spontaneous with ΔG values(ATV = -43.39 kJ/mol, DRV = -41.39 kJ/mol and LPV = -50.51 kJ/mol). The values also indicated that LPV complexed with HIV-1 is more a stable complex. Also, all the binding reactions were exothermic as indicated by the negative ΔH values of ATV = -45.54 kJ/mol, DRV = -55.62 kJ/mol and LPV = -54.71 kJ/mol. The entropy of all the reactions were determined to be unfavourable with the -T∆S of DRV = 14.23 kJ/mol followed by LPV: 4.2 kJ/mol and ATV: 2.15 kJ/mol. Overall this suggested that all the binding reactions were enthalpically driven. Furthermore, the three-dimensional structure of the HIV-1 subtype C protease was elucidated using X-ray crystallography. The three-dimensional structure the HIV-1 CSA (PDB ID: 8CI7) was solved at a 2.4 Å resolution which is better than the 2.7 Å (PDB ID: 3U71) initially solved in our lab. The high-resolution three-dimensional structure of the protease will provide precise information about the arrangement of atoms within the protease molecule, thus enabling the design and development of protease inhibitors that will be specific for the subtype C protease. This study emphasised the significance of investigating subtype C protease in the context of enzyme kinetics, thermodynamics and detailed X-ray crystallography.
A dissertation submitted in fulfilment of the requirements for the degree Master of Science, to the Faculty of Science, School of Molecular and Cell Biology, University of the Witwatersrand, Johannesburg, 2023.
Keywords: HIV-1 subtype C protease; Cloning; Purification; Characterisation; Kinetics; Thermodynamics; Crystallisation; UCTD; SDG-3: Good health and well-being